Investigating Job Satisfaction Using Exploratory Factor Analysis at ABC Factory - N. H. Wan Abdul Aziz, W.; Zulkipli, F.; H. Mohammad Hamzah, M.; W. Azhar, F.; K. N. Abdul Rahim, S. (International Journal of Engineering and Technology, 2018)
The aim of this research is to study the workforce allocation at ABC Factory. A set of questionnaire consists of two parts, which are background of respondent and job satisfaction components were distributed among 80 employees. The statistical method exploratory factor analysis (EFA) was used to classify the components. As a result, the research revealed that there are three main components which are work environment, productivity, and organization can be classified by 25 questions.Â Â
Keywords: Exploratory Factor Analysis; Job Satisfaction; Organization; Productivity; Work Environment.